ZAPIN VILLAGE AND ACTOR RELATIONSHIPS: CULTURE-BASED TOURISM GOVERNANCE IN BENGKALIS, RIAU, INDONESIA - Risma Junita (Jurnal Sosiologi Dialektika Sosial, 2025)
Tourism is a critical driver of economic growth, with rising demand for rural destinations grounded in cultural heritage. This study analyses actor relations in the development of culture-based tourism villages, using Kampung Zapin, Meskom, Bengkalis as a case. A qualitative descriptive design was employed, combining participant observation, and document analysis. Data were coded thematically to identify patterns of interaction, stakeholder roles, and governance strategies. Results show that internal actors, local communities and village administrations interact with external actors, including government agencies and tourism organizations, through overlapping yet complementary roles. Collaborative efforts focus on optimizing resources, seizing market opportunities, and addressing weaknesses. These findings highlight a governance strategy that integrates local strengths, namely kampung zapin, as a Malay tradition and custom, with institutional support, and offers a replicable model for visiting culture-based tourism villages. Zapin, as part of Malay culture, has proven to attract both national and international tourism. This research contributes to the literature on tourism governance and provides policy insights for enhancing rural tourism competitiveness in Indonesia and beyond.